Typologies of the Understanding of the Experience Notion in Pedagogy - Waga, Leszek (Przegląd Badań Edukacyjnych (Educational Studies Review), 2019)
The aim of this paper is to present possible typologies of experience and to point out the need to allow for the multidimensionality of experience categories in pedagogical research. Since experience is primarily a philosophical concept, the first section presents a generally acceptable definition of experience. The second section refers to the main philosophical, epistemological and methodological typologies of experience. The last of the typologies which may be of particular use in pedagogy has been discussed in the third section. It describes experience as an activity, its production (result), and a way of perceiving something. This typology organises the types of understanding experiences in pedagogical literature, considering all the elements of the educational relation. Reflections on the understanding of experience in pedagogy lead to the conclusion that the discipline cannot ignore different typologies of experience or the multidimensional contexts of its occurrence and experience itself turns out to be the category that integrates different levels of pedagogical knowledge. At the same time, it was confirmed that one may not analyse ontological, epistemological and methodological concepts or categories in pedagogy in isolation from philosophical considerations. Otherwise, one may be exposed to ignorance or unjustified simplifications.